A 3D kinematic analysis of the volleyball jump serve - Coleman, S. (coachesinfo.com, 1997)
The serve is the first attacking weapon in the modern game of volleyball. Since the late 1980's (although pioneered by the Brazilians a decade earlier), the most powerful form of service has been the 'jump', or attack, serve. Therefore, it was the aim of this study to provide descriptive kinematics of some of the biomechanical factors involved in the 'jump' serve. Furthermore, these data could then be compared with results from studies examining the attack smash (spike). In summary, the 'jump' or attack serve demonstrated many of the same features as the spiking action. This was unsurprising, given the similarities between the two actions. The main differences were the time difference between the dominant and non-dominant leg extensions and the centre of mass horizontal velocity at take-off. These factors reflected the greater amount of linear translation required in the serve. Trunk rotations again seemed to be unimportantin generating ball speed, whereas elbow and humerus extension were significant factors in this respect. It is intended that the results obtained from this study will be used in a mathematical model (such as those which have been developed for the spike) to examine tactical effectiveness.